Employee Engagement : a Research Overview. - Shuck, Brad (State of the art in business research., 2019)
The field of employee engagement has experienced unprecedented growth over the last three decades. Despite remarkable progress in both practice and scholarship, there remains tremendous confusion about what employee engagement is, what it means, and how organizations can take proactive steps to harness the full power of an engaged workforce. This short-form book provides readers a unique and research-based road map through the rapidly evolving research around employee engagement, including the identification of key literature and theory along with expert, timesaving connections to how theory has informed practice. The author covers the various disciplinary approaches and schools of thought, thematically bridging scholarly literature - including and identifying the historically significant and most current - to better understand how the research is evolving and what new opportunities for scholarship are emerging. Essential reading for scholars of human resource management, leadership and management more broadly, the book is also a valuable read for reflective practitioners globally.